HOWARE EMPLOYMENT AND INCOME INFLUENCE SOCIETY ATTITUDE TO PAY ZAKAT IN SOUTH SUMATERA WITH TAWHIDI PERSPECTIVE - Lily Rahmawati Harahap; Dwi Eka Novianty; Sri Ermeila (S1 Accounting Department, Faculty of Economic, Universitas Pamulang., 2018)
The purpose of this article is to share about how important zakat fund which collected and distributed well, according to the rule based on Islam, in order to improve economic. The phenomena in South Sumatera shows unsycnchronized data between Gross Regional Domestic Product and poverty level. South Sumatera province is the top 11 rankings from34 provinces in Indonesia in terms of GRDP acquisition. But in reality, South Sumatera also the top 18 rankings from 34 provinces in Indonesia in terms of poverty level. This research will discuss the phenomena from society attitude with some factors that might influence, from the tawhidi perspective. Using primary data from 4 regencies and 1 city in South Sumatera and also supported by 2 factors (employment and income), thisresearch describe how are these 2 variables influence society attitude to pay zakat viewed from tawhidi perspective. The result of hypothesis test by using regression model shown that employment variable and income variable influence society attitude to pay zakat simultaneously and partially. With Tawhidi String Relation methode by induced these 2 variables with tetha (θ) will change the result in the good range.